2008
DOI: 10.1111/j.1467-9310.2008.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of office layout on communication in a science‐driven business

Abstract: Driving innovation and creativity has relied heavily on new information technologies in the last decade. Human capital has certainly had its importance, but how to coordinate human capital in order to push productivity in research and development without compromising individual initiative is still not well understood. In this paper, we provide results showing that geometry of workspace has indeed an impact on communication patterns and may thus be used as a means to drive both innovation and efficient research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
2
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 52 publications
2
108
2
12
Order By: Relevance
“…Research results are also inconsistent regarding whether A-FOs lead to increased distractions (De Been & Beijer, 2014;Seddigh et al 2014). Furthermore, while some studies report that A-FO solutions lead to increased communication (e.g., Boutellier et al, 2008;van der Voordt, 2004;Vos & van der Voordt, 2002), others report decreased communication (De Been & Beijer, 2014;Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research results are also inconsistent regarding whether A-FOs lead to increased distractions (De Been & Beijer, 2014;Seddigh et al 2014). Furthermore, while some studies report that A-FO solutions lead to increased communication (e.g., Boutellier et al, 2008;van der Voordt, 2004;Vos & van der Voordt, 2002), others report decreased communication (De Been & Beijer, 2014;Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The previous discussion shows that all the activities held by the enterprise have stages of predominantly individual work as well as stages of predominantly group work. Organizations with multi-space-with many spaces to individual or group activities-are ideal, with places to divergent and FACILITIES PLANNING FOR A CREATIVE COMPANY 445 convergent, individual, or group thoughts (Haner, 2005;Boutellier et al, 2008), in other words, supporting all the stages of the organizational creative process. The existence of multi-spaces breaks the monotony and is positive for creative work (Boutellier et al, 2008).…”
Section: Relationship Diagram and Layout Alternativesmentioning
confidence: 99%
“…The industrial role of the facility layout problem is wide spread and can be found in numerous references in the literature (e.g., Yang, Su, & Hsu, 2000;Chien, 2004;Van Donk & Gaalman, 2004;Wiyaratn & Watanapa, 2010;Ojaghi, Khademi, Yusof, Renani, & Hassan, 2015). Comparatively, there are few studies that deal with the services organizations (Block & Stokes, 1989;Brooks, 1998;Augustin & Brand, 2001;Brennan, Chugh, & Kline, 2002;Boutellier et al, 2008;Danielsson & Bodin, 2008) and none of those has tried to apply layout solution methods to creative facilities yet. In order to accomplish this, the Systematic Layout Planning (SLP) (Muther, 1973) method is used as a mean to close these gaps left by the creative spaces researches.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The physical workplace may be designed to aid collaboration and knowledge sharing both between and within groups (Vischer 2007;Elsbach and Bechky 2007;Coradi et al 2015a;Boutellier et al 2008;Stryker et al 2012). Recently, a team of researchers from Harvard University found that CWs designed to foster workplace mobility can positively affect innovation by increasing the number and frequency of impromptu meetings among employees (Waber et al 2014).…”
Section: Physical Layout and Facilitiesmentioning
confidence: 99%